Translation, cultural adaptation to Brazil and validation of the venous leg ulcer quality of life questionnaire (VLU-QoL-Br) - Araújo,Renata Boldrin de (2014)
Objective: translating the Venous leg ulcer quality of life questionnaire (VLU-QoL), and culturally adapting it to Brazilian Portuguese and validate it with patients at the Hospital das Clínicas of the Botucatu Medical School - Unesp. Methods: the questionnaire was translated by a professional translator and two dermatologists specialized in the area of venous ulcers (VU), reformulated in a meeting of the three translators. The construct (VLU-QoL-Br) was submitted to pre-interviews with ten VU patients for adaptation of the language. Subsequently, it was applied to patients at the HC-Unesp, and for test-retest reliability for verification of its reproducibility. Results: 82 patients were evaluated, with 56 (68%) women. The age average was 67.3 years. The questionnaire was translated, adapted and applied to the patients. The construct presented high internal consistency (alpha = 0.94) and adequate item-total correlation. When the 32 retests were evaluated, an intra-class correlation was noted for concordance of 0.78 (p<0.01), indicating good reproducibility of the construct. The confirmatory factor analysis corroborated the dimensions of the original questionnaire: activities, psychologies, and symptoms. VLU-QoL-Br scores were associated, independently, to the total area of the ulcers and a lower education level of the subjects (p<0.01). Conclusion: the translation, adaptation and validation of the VLU-QoL-Br questionnaire were concluded, demonstrating good psychometric performance, and enabling its clinical use in Brazil. It is important to evaluate its performance in other regions and different samples of individuals.